A systems approach to understanding the identification and treatment of sport-related concussion in community rugby union. (October 2019) - Clacy, Amanda; Goode, Natassia; Sharman, Rachael; Lovell, Geoff P.; Salmon, Paul
Abstract: Aim: The aim of the present study was to utilise a systems thinking approach to explore the perceived responsibilities for identifying and treating concussion held by different actors across the community rugby system (e.g., players, coaches, parents, medics, referees, and management), as well as their role-specific concussion management strategies. Methods: A systems approach was taken to assess what different stakeholders within rugby systems perceive their roles to be regarding concussion identification and treatment. Through an online survey, 118 members of the amateur (community) rugby union system were asked about their role-specific concussion management responsibilities and strategies. Respondents included players, parents, medics, coaches, club managers, administrators, and volunteers. Results: The majority of respondents indicated that they were able to identify the symptoms of rugby-related concussion, however, only medics stated their responsibility to use formal concussion assessments (e.g., SCAT2). A smaller number of the respondents indicated that they were involved in treating concussion within their current role/s (majority of which were medics). Conclusions: This study illustrated that the current challenges in the identification and treatment of rugby-related concussion in community sport may be due to role/responsibility confusion and possible overreliance on field-side medics. These findings offer insight into the possible limitations of the current concussion management guidelines and may offer empirically based direction for future revisions. Highlights: Taking a systems approach, responsibilities for identifying and treating concussion in community rugby union are explored. 93% of respondents from each level of the system indicated that they were able to identify the symptoms of concussion. Half of the club management and 24% of players did not identify a responsibility to identify concussion within their roles. A system-wide reliance on medical aides to both identify and treat concussion was identified. This study offers insight into specific junctures within the rugby system which may be dislocating concussion management.